2016
DOI: 10.1002/ijc.30182
|View full text |Cite
|
Sign up to set email alerts
|

Association of WT1 IgG antibody against WT1 peptide with prolonged survival in glioblastoma multiforme patients vaccinated with WT1 peptide

Abstract: We previously evaluated Wilms’ tumor gene 1 (WT1) peptide vaccination in a large number of patients with leukemia or solid tumors and have reported that HLA‐A*24:02 restricted, 9‐mer WT1‐235 peptide (CYTWNQMNL) vaccine induces cellular immune responses and elicits WT1‐235‐specific cytotoxic T lymphocytes (CTLs). However, whether this vaccine induces humoral immune responses to produce WT1 antibody remains unknown. Thus, we measured IgG antibody levels against the WT1‐235 peptide (WT1‐235 IgG antibody) in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 50 publications
4
49
1
Order By: Relevance
“…In contrast to the detection of CTL responses, the measurement of IgG has several benefits, ie, it is easier and more robust than the time‐consuming CTL assay. Several research groups are thus using the IgG response as a prognostic biomarker for vaccine therapy …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the detection of CTL responses, the measurement of IgG has several benefits, ie, it is easier and more robust than the time‐consuming CTL assay. Several research groups are thus using the IgG response as a prognostic biomarker for vaccine therapy …”
Section: Discussionmentioning
confidence: 99%
“…17,28 The increase in Table 1). MR, molecular remission; NLS, nuclear localization signal; undef, undefinable; UTR, untranslated region.…”
Section: Immunomonitoringmentioning
confidence: 94%
“…We previously reported that the combination of positive DTH to WT1 peptide and WT1-235 IgG antibody production was a better predictor of prolonged PFS and OS, compared to either of them alone, in patients with recurrent glioblastoma. 31 The results presented in the present study show that WT1 peptide vaccine failed to induce both of the immune responses in the majority of patients enrolled in the trial. These findings indicate that the induction of WT1-specific immune responses by the current WT1 peptide vaccine is unsatisfactory in patients with thymic malignancies, which led us to believe that a more robust induction of WT1specific anti-tumor immune responses is required for achievement of better clinical outcomes in thymic epithelial malignancies treated with WT1 peptide vaccine immunotherapy.…”
Section: Discussionmentioning
confidence: 55%